Diagnostic challenges in gastrointestinal stromal tumors: a case report of concurrent gastrointestinal stromal tumor, lymphangioma, and solid pseudopapillary neoplasm of the pancreas - Gustafson, Alexandra M.; Perati, Shruthi R.; Arikan, Evsen A.; Lin, Wanrun; Satterwhite, Audra A.; Canady, Stephanie N.; Ahn, Diane S.; Sullivan, Molly A.; Joyce, Stacy R.; Quezado, Martha; Davis, Jeremy L.; Blakely, Andrew M. (Journal of Gastrointestinal Oncology, 2026)
Gastrointestinal stromal tumors (GISTs) are mesenchymal tumors of the gastrointestinal tract which arise from the interstitial cells of Cajal. Nearly half of all patients present with advanced disease. GISTs can have a solid, cystic, or mixed morphology, sometimes appearing similar to other pathologies on imaging, making diagnosis of metastatic GIST difficult.